Evidence That an Acute Increase in Glomerular Filtration Has Little Effect on Sodium Excretion in the Dog unless Extracellular Volume is Expanded - Lindheimer, Marshall D. (1967)
The concept that acute increases in glomerular filtration rate (GFR) will cause large concomitant increases in sodium excretion has been re-examined. In previous work, GFR was elevated by volume expansion, usually with saline infusions. Recent evidence shows that tubular reabsorption is depressed during saline loading; hence, the independent effect of increased GFR on sodium excretion cannot be assessed. To determine the effect of acute increases in GFR per se on sodium excretion, we raised GFR by four techniques not involving volume expansion: protein feeding, dopamine infusion, intravenous dexamethasone, and cross-circulation. GFR increased acutely by 5 to 85% in these experiments. In 12 of 24 experiments, GFR increased by more than 30%. In all but one experiment, sodium excretion increased by less than 75 μEq per minute. Data from experiments using each of the four techniques were comparable. The results were the same whether mineralocorticoid activity was high or low. In contrast, during saline loading, sodium excretion increased more than 800 μEq per minute with equal or lesser changes in GFR. These results demonstrate that acute increases in GFR per se have little effect on sodium excretion. We suggest that, due to constant fractional sodium reabsorption in the proximal tubule (glomerulotubular balance) and increased distal reabsorption, virtually all of the increase in filtered sodium is reabsorbed when GFR increases. Depression of tubular reabsorption is required for natriuresis.